Numerical simulation of seismicity potential resulting from the injection of CO2 into depleted reservoir in Wilbarger County field, Texas - Dorcas S. Eyinla; Hossein Emadi; Steven K. Henderson; Humza Bin Navaid; Abir Kebir; Aman Arora (Petroleum, 2025)
Fluid injection in fractured rocks presents significant challenges requiring the integration of various elements to account for reservoir property heterogeneities. To understand magnitude of potential seismic risks resulting from CO2 injection in naturally fractured sand reservoirs in the study location, we devised a simulation model which utilizes a coupled thermo-hydro-mechanical (THM) approach, encompassing different injection scenarios and reservoir injection systems. The model effectively captures the complex interplay between geological features and fault failure processes. Furthermore, we examined the mechanical response of the caprock under constant injection rates by analyzing the evolution of shear stress and its impact on permeability enhancement. Our findings reveal that the pressurization effect of fluid and stress alterations trigger significant fault rupture, leading to seismic events of varying magnitudes. The extent of seismic activity hinges on the reservoir's initial state, the properties of the overlying caprock, and the injected volume. Moreover, we discovered that deformations within the caprock layer are most pronounced near fault zones, gradually diminishing with distance from these zones. Notably, the degree of permeability modification in the caprock is linked to the magnitude of shear stress. Additionally, our research corroborated that higher injection rates markedly accelerate fault slip, albeit with minimal impact on the extent of permeability enhancement. However, we noted a non-linear relationship between seismic activity and fluid injection rates, suggesting that the magnitude of seismic consequences is contingent upon the temporal analysis of various parameters. These significant findings offer valuable insights into understanding the intricate processes associated with subsurface injection, which often manifest in phenomena such as fault ruptures and induced seismicity.